2018
DOI: 10.18203/2349-3291.ijcp20183878
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of urinary tract infection among children

Abstract: Urinary tract infection is the third most common cause of febrile illness among children. UTI carries a considerable morbidity among this vulnerable age group because of its potential complications (e.g. hypertension and renal failure). Because diagnosis of UTI among the pediatric age group is challenging if solely based on clinical setting, knowledge of the actual prevalence rates of UTI among children is essential for pediatricians to determine the cost benefit effect of requesting investigations for suspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…The guideline recommends that the choice of agent is also based on local antimicrobial sensitivity patterns and should later be adjusted according to sensitivity-testing of the isolated uropathogen. Frequently used antibacterial substances for UTI therapy in infants and children were cephalosporins, trimethoprim or trimethoprim/sulfamethoxazole, ampicillin, amoxicillin, amoxicillin/clavulanic acid, tobramycin, gentamicin, ciprofloxacin, and nitrofurantoin [8]. Our investigation also found a similar pattern of etiological uropathogens and antibacterial agents, with some uropathogen heterogeneity and antibacterial resistance.…”
Section: Discussionsupporting
confidence: 71%
“…The guideline recommends that the choice of agent is also based on local antimicrobial sensitivity patterns and should later be adjusted according to sensitivity-testing of the isolated uropathogen. Frequently used antibacterial substances for UTI therapy in infants and children were cephalosporins, trimethoprim or trimethoprim/sulfamethoxazole, ampicillin, amoxicillin, amoxicillin/clavulanic acid, tobramycin, gentamicin, ciprofloxacin, and nitrofurantoin [8]. Our investigation also found a similar pattern of etiological uropathogens and antibacterial agents, with some uropathogen heterogeneity and antibacterial resistance.…”
Section: Discussionsupporting
confidence: 71%
“…This prevalence is comparable to many studies Shaikh N et al, [8] and Bauchner et al [9], showed prevalence range from 1.2% to 8%. As per Almofarreh M et al study, gender is the commonest influencing factor of UTI [10]; the studies also reported that the prevalence of UTI is more in female children [11,12,13]. The anatomical structure as well as less distance with anal region is the main reported cause for more prevalence of UTI among female children.…”
Section: Discussionmentioning
confidence: 76%
“…2 The risk of infection can be augmented in certain conditions, such as age under 3 months, uncircumcised males, malnutrition, and constipation. 3 The prevalence of urinary tract infections in children by antibiotic-resistant bacteria has been reported in many studies. For instance, Nazmi et al, revealed that an overall prevalence of UTI caused by ESBL Escherichia coli and Klebsiella pneumoniae were 35% and 45%, respectively, in a private hospital in Tangerang.…”
Section: Introductionmentioning
confidence: 99%